Numerical Study Via Finite Element Analysis of the Structural Behavior of Rigid Pavement of Aerodromes - Albert Willian Faria (E&S Engineering and Science, 2020)
The present study develops a 3D numerical model of the concrete pavement system of aerodromes in contact with the main landing gear of aircrafts using Finite Element Method (FEM). The pavement system used in the analysis consisted of six concrete slabs overlaying a subgrade medium with stiffness k. Doweled bars are considered for the pavement transverse joints while aggregate interlocks are considered for longitudinal joints. A parametric study was conducted to validate the model numerically, as well as to investigate the influence of the doweled bars, aggregate interlocks and subgrade stiffness on the pavement deflections when it is subjected to a dynamic load. About 77% decrease in deflection was attained due to the presence of doweled bars. This study additionally presents a methodology for designing the pavement thickness and the compressive strength of concrete based upon the Mohr-Coulomb’s failure criterion. It is found that for a pavement thickness of 0.305m the minimum compressive strength of concrete should be 28 MPa.